Designing Academic Data Visualization Dashboard Using Google Data Studio at SMPN 8 Pariaman - M. Dyon; Karmila Suryani; Rini Widyastuti; Ade Fitri Rahmadani (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to use Google Data Studio to produce an academic data visualization dashboard system to display information, which can manage academic data, namely teacher attendance data and student grades, to provide decision-making support for decision makers in the monitoring process and evaluate school internal processes and monitor student grades at SMPN 8 Pariaman School. The type of research used is the R&D (Research and Development) approach SDLC (Systems Development Life Cycle) method with a prototype model. The stages carried out are communication, planning, modeling, construction and handover (handover). The system testing method studied uses questionnaire guidelines for functional testing to test system functionality to verifiers and usability testing to test system usability and suitability of functions and services to users. Based on the results of the validator functional test study, the results of meeting the functional requirements with both a value of 1 and 89% of the feasibility value of the system usability test are classified as very feasible. Therefore, it can be concluded that the academic data visualization dashboard system using Google Data Studio meets the requirements and is very suitable as a support for SMPN 8 Pariaman School in processing academic data on teacher attendance and student grades.